Effects of Urbanization on Storm Water Run-off : A Case Study of Kathmandu Metropolitan City, Nepal - Bajracharya, Ashim Ratna; Rai, Ritu Raj; Rana, Shreema (Journal of the Institute of Engineering, 2016)
In urban and suburban areas, much of the land surface is covered by buildings and pavements, which do not allow precipitation and snowmelt to soak into the ground. Instead, most developed areas rely on storm drains to carry large amounts of runoff from roofs and paved areas to nearby waterways. Hard surfaces such as streets, parking lots and built-up areas are impervious surfaces through which, water cannot pass through. As more and more landscapes are covered with hard impervious surfaces, the amount of water that infltrates, decreases and the amount that runs off, increases. This research is focused on studying run-off conditions in context of urban areas. The study area is Kathmandu Metropolitan City (KMC). The City is in the stage of rapid urbanization and with it, a rapid increase in built-up spaces. As a result, the city is losing a balance between impervious and pervious cover. Loss of greeneries and unpaved open spaces are causing rapid drain of rain-water. This is creating a disturbance in the hydrological cycle of the area. For assessing the extent of runoff, total runoff was estimated of KMC, as per the surface characteristics and using rational method for calculation. Parameters for determining run-off coeffcients were mainly land cover and land use data, soil type and slope of surface. Results show that current runoff is alarmingly high, indicated by the difference between the run-off values of pre and post-development scenarios. Urban development pattern has caused a major impact, in the prevailing run-off and it is very crucial that these issues are addressed in urban planning to promote effective solutions for maintaining water cycle and water resources in urban areas. Journal of the Institute of Engineering, 2015, 11(1): 36-49